Interaction of glycine, lysine, proline and histidine with dipalmitoylphosphatidylcholine lipid bilayers: a theoretical and experimental study - Porasso, Rodolfo Daniel (2015)
The interaction of unblocked glycine, lysine, proline, and histidine (in their three forms, namely two tautomers and the protonated form) with a dipalmitoylphosphatidylcholine (DPPC) bilayer was assessed using extensive atomistic molecular dynamics simulations. Free energy profiles for the insertion of each amino acid into the lipid bilayer were computed along an appropriated reaction coordinate. The simulation results for glycine in the presence of DPPC were compared with experimental data obtained by Fourier transform infrared spectroscopy. Experimental results predict, in good agreement with simulations, the existence of intermolecular interactions between the DPPC head groups and glycine. Atomistic simulations were further extended to investigate the free energy profiles for lysine, proline and histidine, leading to the following conclusions: (i) lysine free energy profiles computed using a united atom force-field and an analog molecule, where the side-chain is truncated at the β-carbon atom, differ significantly from each other; (ii) the free energy profiles for the three forms of histidine are all very similar, although the charged form interacts mostly with the carbonyl groups of DPPC, while the tautomers interact with the phosphate groups; and (iii) proline does not show a minimum in the free energy profile, pointing to the absence of binding to the membrane lipids. Overall, this work contributes to our general understanding of the various factors affecting the interactions between amino acids and a model cell membrane, and may spur progress in the effort to develop new molecular models to study larger biological systems.